Captain Awesome and the new kid - Kirby, Stan (Captain Awesome ;, 2012)
Eugene McGillicudy stands up for Sally Williams, the new student at Sunnyview Elementary, and then discovers that they both like an orange cat named Mr. Whiskersworth and the comic book super hero, Super Dude.